Longevity of Carduus nutans, Datura ferox, Anoda cristata y Sorghum halepense seeds - Faccini, Delma; Giuggia, Ester; Ruiz, Alicia; Allieri, Luiz; Mitidieri, Augustin (Pesquisa Agropecuaria Brasileira, 1992)
An experiment was conducted to study the seed longevity of spurred anoda (Anoda cristata), large thornapple (Datura ferox), Johssongrass (Sorghum halepense) and muskthistle (Carduus nutans as affected by depth of burial in a non-cultivated soil with natural cover. A complete randomized design with four replications was used. The burial depths were 0,0; 7,5; 15 and 22,5 cm. Percentage recovered seeds, germination percentage and viability percentage. The percentage of seeds recovered decreased in all treatments and for all species except for Datura ferox. In Carduus nutans viability decreases sharply at 41 months for all depths. In Datura ferox viability decreases noticeably at 6 months. In Anoda cristata the germination percentage remains low till 53 months. In Sorghum halepense the germination percentage is low at 6 months of burial; from 41 months on, the values of germination percentage and viability are similar.